(3efJgi GdShd aj TQM GdaUhds - (3Ydj Hf jhfS GdYGedj GdHfWjs; (3CHh LYaQ GdWhSj , CHh LYaQ eMeO Hf GdMSf Hf Ydj GdWhSj, CHh LYaQ GdWhSj,J (B460 (3g` s
(3ChdgG (B:s
(3hHYO agPG cJGH loefJgi GdShd aj TQM GdaUhd GdJj UfagG CHhLYaQ eMeO Hf eMeO Hf GdMSf GdWhSj s
(3BNQgG (B:s
(3hQRbfG Gddg hEjGce ef SYGOI GdOGQ GdBNQI Je hGdMeO ddg hUdi Gddg Ydi SjOfG eMeO hBdg hUMHg hSde s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds